E-Services Opportunities and Threats - Journal of Value Chain Management, Vol. 1, No. 1/2 (Special Issue) - Evanschitzky, Heiner.; Evanschitzky, Heiner.; Iyer, Gopalkrishnan R.; Iyer, Gopalkrishnan R. (Applied Marketing Science / Angewandte Marketingforschung,, 2007)
This volume presents the best papers of the special issue ‘E-Services’ of the Journal of Value Chain Management. In association with the Marketing Center Muenster (University of Muenster, Germany) and the Center for Services Marketing and Management (Florida Atlantic University, USA), the volume provides a thorough introduction and systematic overview of the new and emerging field ‘E-Services’. A group of well-known authors from around the world discuss the state-of-the-art of the research and development in various aspects of ‘E-Services’ including E-Commerce, international aspects of electronic services, growth through E-Services, satisfaction and loyalty in electronic markets, and service engineering.